mitigasi penuruan tegangan dengan liquid untuk starter motor pada sistem PT Solusi Bangun Indonesia TQ 1 - Wijanarko, Rahmat Febrianto (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2024)
Voltage stability is one of the main concerns in the electric power system. One of them is related to the voltage sagging problem. The cause of voltage stability problems in the electric power system is the motor starting event. The current motor starting method that is often used is to use a VFD soft starter. There is another method to mitigate voltage sagging problems during motor starting events using the liquid starter technique which is still rarely used. The simulation results obtained show that by using a liquid starter there is a slight decrease in the voltage profile, low starting current, smooth start, little impact on the grid. This was proven in the application of a liquid starter using etap software and Matlab plotting. The smallest value of the voltage profile was 90.35% and the starting current was 6 times lower than the direct online method. From this application, the liquid starter method has proven to be much more effective in overcoming high voltage and current sags during motor starting events.